A systematic review of midwives’ training needs in perinatal mental health and related interventions - Dubreucq, Marine; Dupont, Corinne; Lambregtse-Van den Berg, Mijke P.; Bramer, Wichor M.; Massoubre, Catherine; Dubreucq, Julien (Frontiers in Psychiatry, 2024)
Background Midwives may be key stakeholders to improve perinatal mental healthcare (PMHC). Three systematic reviews considered midwives’ educational needs in perinatal mental health (PMH) or related interventions with a focus on depression or anxiety. This systematic review aims to review: 1) midwives’ educational/training needs in PMH; 2) the training programs in PMH and their effectiveness in improving PMHC. Methods We searched six electronic databases using a search strategy designed by a biomedical information specialist. Inclusion criteria were: (1) focus on midwives; (2) reporting on training needs in PMH, perinatal mental health problems or related conditions or training programs; (3) using quantitative, qualitative or mixed-methods design. We used the Mixed Methods Appraisal Tool for study quality. Results Of 4969 articles screened, 66 papers met eligibility criteria (47 on knowledge, skills or attitudes and 19 on training programs). Study quality was low to moderate in most studies. We found that midwives’ understanding of their role in PMHC (e.g. finding meaning in opening discussions about PMH; perception that screening, referral and support is part of their routine clinical duties) is determinant. Training programs had positive effects on proximal outcomes (e.g. knowledge) and contrasted effects on distal outcomes (e.g. number of referrals). Conclusions This review generated novel insights to inform initial and continuous education curriculums on PMH (e.g. focus on midwives’ understanding on their role in PMHC or content on person-centered care). Registration details The protocol is registered on PROSPERO (CRD42021285926)